2021
DOI: 10.3390/jdb9030033
|View full text |Cite
|
Sign up to set email alerts
|

Molecular Pathology Demonstration of SARS-CoV-2 in Cytotrophoblast from Placental Tissue with Chronic Histiocytic Intervillositis, Trophoblast Necrosis and COVID-19

Abstract: A subset of placentas from pregnant women having the SARS-CoV-2 infection have been found to be infected with the coronavirus using molecular pathology methods including immunohistochemistry and RNA in situ hybridization. These infected placentas can demonstrate several unusual findings which occur together—chronic histiocytic intervillositis, trophoblast necrosis and positive staining of the syncytiotrophoblast for SARS-CoV-2. They frequently also have increased fibrin deposition, which can be massive in some… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
16
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 19 publications
(16 citation statements)
references
References 55 publications
(78 reference statements)
0
16
0
Order By: Relevance
“…In those placentas where the virus was localized using either immunohistochemistry or RNA in situ hybridization, the syncytiotrophoblast was involved in all cases. Previous studies have indicated that although the syncytiotrophoblast is the most common placental type to be involved with SARS-CoV-2, 59 other villous cells including cytotrophoblast, 61 Hofbauer cells, 60 and endothelial cells 60 can also stain positively for the virus. In our series, cytotrophoblast, Hofbauer cells and villous stromal and endothelial cells were occasionally found to stain positively for SARS-CoV-2.…”
Section: Discussionmentioning
confidence: 99%
“…In those placentas where the virus was localized using either immunohistochemistry or RNA in situ hybridization, the syncytiotrophoblast was involved in all cases. Previous studies have indicated that although the syncytiotrophoblast is the most common placental type to be involved with SARS-CoV-2, 59 other villous cells including cytotrophoblast, 61 Hofbauer cells, 60 and endothelial cells 60 can also stain positively for the virus. In our series, cytotrophoblast, Hofbauer cells and villous stromal and endothelial cells were occasionally found to stain positively for SARS-CoV-2.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, SARS-CoV-2 RNA is rarely detected in the placenta, and electron microscopy has misidentified common subcellular structures as coronavirus particles ( 25 28 ). In this patient, we found neither evidence of placental SARS-CoV-2 infection by ISH or IHC ( 29 34 ) nor evidence of chronic histiocytic intervillositis, which has been identified as a relatively consistent pathologic feature associated with placental SARS-CoV-2 infection ( 32 34 ). Consequently, conventional RT-PCR positivity may represent maternal viremia.…”
Section: Discussionmentioning
confidence: 57%
“…A recent study showed SARS-CoV-2 staining in the placental cellular layers during embryonic development [57]. Positive staining for SARS-CoV-2 was detected in the epithelial covering of the placental villi called the syncytiotrophoblast, as well as in the inner cellular layer that gives rise to it, called the cytotrophoblast [57].…”
Section: Impact Of Covid-19 On Fetal Development and Childrenmentioning
confidence: 99%
“…A recent study showed SARS-CoV-2 staining in the placental cellular layers during embryonic development [57]. Positive staining for SARS-CoV-2 was detected in the epithelial covering of the placental villi called the syncytiotrophoblast, as well as in the inner cellular layer that gives rise to it, called the cytotrophoblast [57]. This study is the first to report the details of the participation of the cytotrophoblast in the SARS-CoV-2 infection process, which adds to the list of fetal cell types from the placentas of infected mothers where viral staining is detected [57].…”
Section: Impact Of Covid-19 On Fetal Development and Childrenmentioning
confidence: 99%
See 1 more Smart Citation